The people's peace : Britain since 1945 / Kenneth O. Morgan. - Morgan, Kenneth O. (Oxford University Press, 2021)
This comprehensive study of British history since 1945 has been fully updated and expanded for this edition to include a chapter on the rise of New Labour.